An inflammatory myofibroblastic tumor of the urinary bladder in a young girl presenting as acute kidney injury due to obstructive uropathy - Umesh, L; Shivaprasad, SM; Niranjan, MR; Sathish Kumar, MM; Leelavathi, V; Sridhara, CG (Asian Journal of Medical Sciences, 2015)
Inflammatory myofibroblastic tumor (IMT) of the bladder is an uncommon benign tumor of the urinary bladder, which is of unknown neoplastic potential, characterized by spindle cell proliferation with characteristic fibro inflammatory and pseudosarcomatous appearance of mesenchymal origin. Myofibroblastic tumor, is also known as inflammatory pseudotumor or pseudosarcoma. Bladder location is very uncommon. We report a case of a young girl who presented with acute kidney injury due to obstructive uropathy. On evaluation found to have Inflammatory myofibroblastic tumor at the base of the urinary bladder, which gradually improved with hemodialysis and successive urological interventions. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12535 Asian Journal of Medical Sciences Vol.6(6) 2015 80-82